Effect of the wheat starch/wheat protein ratio in a batter on fat absorption and quality attributes of fried battered and breaded fish nuggets. Issue 7 (22nd June 2020) - Chen, Chaofan; Chen, Jiwang; Yuan, Zijun; Liao, E; Xia, Wenshui; Wang, Haibin; Xiong, Youling L.
Abstract : Abstract: Battered and breaded fish nuggets (BBFNs) were prepared by treating fish with a batter composed of wheat starch (WS) and wheat protein (WP) blends (at the ratios of 15:1, 13:1, 11:1, 9:1, and 7:1, w/w), frying at 170 °C (40 s) followed by 190 °C (30 s). Fried BBFNs were evaluated for moisture and fat contents, color, shrinkage, acrylamide content, and fat distribution. Results showed that moisture content and brightness ( L * value from colorimetry) increased with a decrease of WS/WP ratio to 11:1 w/w, then decreased as WS/WP ratio further decreased, while fat content, fat distribution level, and shrinkage of fried BBFNs presented opposite results. However, there was a slight influence of WS/WP ratio on yellowness ( b * value), redness ( a * value), and acrylamide content of fried BBFNs. Among WS/WP ratios, fried BBFNs with 11:1 w/w have the highest moisture content (16.43%) and the lowest fat content (23.39%), fat distribution level, shrinkage (10.72%), and acrylamide content (57 mg/kg), while a crust with golden‐yellow color was observed. This study demonstrates that moisture evaporation and fat absorption were significantly influenced by WS/WP ratio in the batter ( P  < 0.05), with the most effective results in quality attributes improvement of fried BBFNs. Practical Application: This study clearly showed that the fat content and quality attributes of fried BBFNs were significantly affected by WS/WP ratio in the batter ( P  < 0.05). The inhibition of fat absorption and improvement of shrinkage and color in fried BBFNs was the most effective for a 11:1 w/w WS/WP ratio.